Tandem organic light-emitting diode - Tan, James Zhi Wei. (2011)
As we know, our world resource is finite and there about six hr of useful time a night every day. That why there a need of new light source with potentially high efficiency and must be environmentally friendly. This is why solid state lighting (SSL) was born. Solid state lighting (SSL) is make up with light emitting diodes (LEDs) or organic LEDs (OLEDs).